PENERAPAN METODE SERVQUAL UNTUK EVALUASI DAN PERBAIKAN KUALITAS PELAYANAN PADA KEGIATAN PENYULUHAN BAHASA INDONESIA PRAKTIS DI BALAI BAHASA PROVINSI SULAWESI UTARA - Kusmara . Jiwantara; Agung . Sutrisno; Johan Stiffen Cartner Neyland (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2013)
This study aims to determine the level of service quality and satisfaction the participant of dissemination the quality of services provided by Balai Bahasa Provinsi Sulawesi Utara. The research is conducted at Balai Bahasa Provinsi Sulawesi Utara from October until December 2012.This study is using the servqual method is an instrument to measure a quality of service. The measurement of the quality of service in the servqual method is based on the five dimensions of services namely tangibles, responsiveness, reliability, assurance, and empathy. This research will measure gap between experienced services and services expected by customers..The method using questionaire which is developed into 12 questions (attributes) that can be used to measure the quality of service and level of satisfaction on the activities of the Disseminasion of Practical Bahasa Indonesia in Balai Bahasa Provinsi Sulawesi Utara. The result quality of service found between the range -0.14 to 0.28 indicating nearly ideal quality of service and level of satisfaction with the value of 88%. That indicates that the participant of dissemination satisfied with the quality of service delivered.Keywords: Quality of Service, Service Quality Method (Servqual), Customer Satisfaction Index